Odczytując sens oryginału (na podstawie przekładu na język serbski i angielski Poematu dla dorosłych Adama Ważyka) - Haneczok, Iwona (Przekłady Literatur Słowiańskich, 2011)
Making out the sense (based on translations of Adam Wazyk’s A Poem for Adults into English and Polish) The article is based on cognitive science and tries to create a prototype of a perfect situation in translation and then categorize two of these situations: a translation from Polish into English and from Polish into Serbian. The prototype is a process in which the translator doesn’t find it difficult to find equivalents and the reader is able to understand the sense of the original. Although this perfect situation is unreal, different situations can be classified as “better” or “worse” representatives of it. As the article focuses on Polish, Serbian and English languages, the conclusion is that the translation from Polish into Serbian is a better representative of the category than the translation from Polish into English as the language relationship of the two former languages is stronger than the relationship between the two latter ones.